Trust Under Threat: The Influence of Fake News and AI Manipulated Content on Mass Media Credibility (Journal of Asian Development Studies, 2026)
The current study aimed to find the influence of fake news and AI-manipulated content on mass media credibility, particularly through social media usage as a moderator, to fill the gap in the literature, as such studies are limited in the cultural context of Pakistan, where awareness regarding digital media use is limited and media illiteracy is very high. The study adopted a cross-sectional correlational study design and purposive sampling technique to collect data from the Pakistan cohort with at least intermediate qualification and ages 18 to 39. The study adopted structured questionnaires to measure variables with reliability ranges from 0.73 to 0.90. The Pearson correlational analysis reported a significant positive relationship between fake news and AI-manipulated content, whereas fake news has a significant negative relationship with media credibility. AI-manipulated content has a significant positive relationship with social media usage and a negative relationship with media credibility. Furthermore, social media usage possesses a significant negative relationship with media credibility. Furthermore, Hayes Macro Process 4.2 reported that social media usage significantly and positively moderated the negative influence of fake news and manipulated content on mass media credibility. The study provided comprehensive implications for youth of Pakistan.